Implementasi Metode Simple Additive Weighting dan Metode Prototipe untuk Perangkingan Guru Terbaik - Nurhadi Nurhadi (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
Some schools currently still use manual methods for assessment in determining the best teachers. Giving grades to teachers is sometimes still subjective, so the risk of conflict is high due to inaccurate and non-transparent assessments, making it a problem for teachers in teaching. For this reason, an information system is needed to get accurate calculation results to get the best teacher ranking. In answering the problems found, the author developed a decision support system using the Simple Additive Weighting method to obtain accurate ranking results so that it can provide maximum decision results through faster, more accurate and precise classification and evaluation. And this research uses a prototype method as an addition to make system development easier. The results of calculations using the SAW method can determine the ranking for the best teachers. Based on a comparison between the pretest and posttest results, it was found that the conformity level was 60% for appropriate data from the 10 data used and 40% for inappropriate data.